Fruit characterization and seed germination of selected dry forest wild edible fruit tree species in North West Ethiopia - Kirubiel Motbaynor; Asmamaw Alemu; Yohannis Gebremariam; Amare Gebeye; Muhabaw Taju (Forest Science and Technology)
Dry forests tree species such as Tamarindus indica and Diospyros mespiliformis are known for their diverse socioeconomic and ecological importance. Tamarindus indica and Diospyros mespiliformis play a critical role in maintaining ecosystem stability and supporting biodiversity, while contributing significantly to local livelihoods through their nutritional and income generation. Despite their actual and potential benefits, conservation of the species has received little attention and the species are being threatened by overexploitation and degradation. This study characterizes fruit and examines the seed quality and determines appropriate pre-sowing treatment for enhanced germination. The seed quality examination was conducted based on the International Seed Test Association (ISTA) standard testing procedures. The germination experiment was laid out in a completely randomized design (CRD) with five pre-sowing treatments (control, cold water, hot water, concentrated sulphuric acid (98%), and nicking) with four replications. The results revealed that the average number of seeds in T. indica and D. mespiliformis fruits varies greatly, averaging 5.55 ± 2.46 and 3.72 ± 0.8 seeds per fruit, respectively. Both the T. indica and D. mespiliformis species have orthodox seeds, with a moisture content of 7.91 ± 0.02% and 6.22 ± 0.02%, respectively. There were 1262–1273 seeds obtained in a kilogram of T. indica with seed purity ranging from 98.39–98.61%. For D. mespiliformis, a kilogram of seed contains 3154–3167 seeds with a purity range of 92.1–92.9%. Thus, based on the result from one kilogram of pure seeds of T. indica and D. mespiliformis, there can be raised 1242-1255 and 2905-2942 seedlings, respectively. The germination percentage, germination index, mean germination time, and germination period of both study species showed significant differences across treatments (P< 0.05), with the exception of D. mespiliformis’ germination period. For T. indica, nicking was resulted in the best germination (100%), followed by sulphuric acid 97.5 ± 4.62%, whereas the lowest germination of 60.0 ± 7.55% was obtained under the control. For D. mespiliformis, sulphuric acid was resulted the highest germination 66.22 ± 4.78%, whereas nicking yielded the lowest germination 10 ± 2.31%. Both species exhibit a physical seed dormancy associated with their hard seed coats. Thus, appropriate pre-sowing treatment is essential to break their seed dormancy and enhance germination. The findings of this study provide valuable insights for improving the germination of the species in nurseries for conservation, propagation and domestication efforts of species and future commercialization initiatives through cultivation. This in turn contributes to maximizing the ecological and food security and local livelihood contributions of these wild edible fruit tree species.